4 Implementation of a structured educational pathway utilising final year student nurses during a pandemic. (30th November 2020) - Paul, Clare; Fletcher, Hannah
Abstract : Rationale: As the significant impact of COVID-19 became apparent, the government and Health Education England (HEE) recognised the vital role students would play throughout the pandemic. Students within 6 months of qualification elected to step into the role of band 4 Aspirant Nurses (ANs), working in a non-supernumerary capacity. Skill gaps, with the potential to impact the AN's ability to work with the required level of autonomy, were identified upon induction. The ANs were supported by the Graduate and Undergraduate teams who collaborated to create a structured educational pathway. The outcome anticipated was to improve retention, decrease supernumerary time and shorten upskilling of newly registered competencies. Description: Preceptorship was introduced, acknowledging the transition from Student to Registered Practitioner and focusing on the required level of autonomy. A mandatory educational pathway included three study days combined with 570 hours of in-situ clinical teaching. These covered an induction to their role, oral and intravenous medication competencies, communication strategies, wellbeing and clinical simulation. Results: All ANs (100%) who completed the programme reported that they found the teaching had a positive impact on their practice and that they would implement it within their role. It is anticipated that the ANs transition to Registered Nurse will be accelerated, reflected in their shorter competency deadlines. Supernumerary time reduced by 50% for those entering new areas of practice whilst those remaining in the same area in which they completed student placement required no formal supernumerary time. The effectiveness of this new role and education strategy will continue to be studied and reported as these ANs qualify and are compared with previous newly qualified cohorts. Whilst the circumstances which led to this teaching program may not be repeated, lessons learnt still have the potential to shape future transition.